(untitled) - Patel, Mukund R. (Florida, 1999)
Wind and Solar Power Systems provides a comprehensive treatment of this rapidly growing segment of the power industry. It provides the fundamentals of wind and solar power generation, energy conversion and storage, and the operational aspects of power electronics and the quality of power. It covers in detail the design, operation, and control methods applicable to stand-alone as well as grid-connected power systems and discusses the present status of and the on-going research in renewable power around the world.
Keywords: Trạm năng lượng gió,Wind power plants,Trạm năng lượng mặt trời,Solar power plants